Associations of Plasma Kynurenines With Risk of Acute Myocardial Infarction in Patients With Stable Angina Pectoris. Issue 2 (February 2015) - Pedersen, Eva Ringdal; Tuseth, Nora; Eussen, Simone J.P.M.; Ueland, Per Magne; Strand, Elin; Svingen, Gard Frodahl Tveitevåg; Midttun, Øivind; Meyer, Klaus; Mellgren, Gunnar; Ulvik, Arve; Nordrehaug, Jan Erik; Nilsen, Dennis W.; et al.
Abstract : Objective—: Enhanced tryptophan degradation, induced by the proinflammatory cytokine interferon-γ, has been related to cardiovascular disease progression and insulin resistance. We assessed downstream tryptophan metabolites of the kynurenine pathway as predictors of acute myocardial infarction in patients with suspected stable angina pectoris. Furthermore, we evaluated potential effect modifications according to diagnoses of pre-diabetes mellitus or diabetes mellitus. Approach and Results—: Blood samples were obtained from 4122 patients (median age, 62 years; 72% men) who underwent elective coronary angiography. During median follow-up of 56 months, 8.3% had acute myocardial infarction. Comparing the highest quartile to the lowest, for the total cohort, multivariable adjusted hazard ratios (95% confidence intervals) were 1.68 (1.21–2.34), 1.81 (1.33–2.48), 1.68 (1.21–2.32), and 1.48 (1.10–1.99) for kynurenic acid, hydroxykynurenine, anthranilic acid, and hydroxyanthranilic acid, respectively. The kynurenines correlated with phenotypes of the metabolic syndrome, and risk associations were generally stronger in subgroups classified with pre-diabetes mellitus or diabetes mellitus at inclusion ( P int ⩽0.05). Evaluated in the total population, hydroxykynurenine and anthranilic acid provided statistically significant net reclassification improvements (0.21 [0.08–0.35] and 0.21 [0.07–0.35], respectively). Conclusions—: In patients with suspected stable angina pectoris, elevated levels of plasma kynurenines predicted increased risk of acute myocardial infarction, and risk estimates were generally stronger in subgroups with evidence of impaired glucose homeostasis. Future studies should aim to clarify roles of the kynurenine pathway in atherosclerosis and glucose metabolism. Abstract : Supplemental Digital Content is available in the text.